2009
DOI: 10.1007/s10327-009-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine crown gall caused by Rhizobium radiobacter (Ti) in Japan

Abstract: In 2005, characteristic symptoms of crown gall on grapevines (Vitis vinifera L. cv. Muscat of Alexandria, and cv. Seto Giants) were observed in a commercial greenhouse-orchard in Okayama Prefecture, Japan. Isolations from diseased tissues consistently yielded bacterial colonies that were white, glistening, and produced abundant polysaccharide on potato semi-synthetic agar (PSA) medium. Ten representative isolates were chosen for further characterization. A multiplex polymerase chain reaction (PCR) assay showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We previously reported that the nonpathogenic R. vitis strain, VAR03-1, which was isolated from a grapevine nursery stock in Japan, inhibited tumor formation caused by several R. radiobacter (Ti), R. rhizogenes (Ti), and R. vitis (Ti) strains isolated from different plants in Japan on grapevines, roses, tomatoes, sunflowers, and apples (18, 19, 21, 22, 23, 25). Repetitive sequence-based polymerase chain reaction (rep-PCR) DNA fingerprint analysis and an analysis of the sequences of three housekeeping genes revealed that VAR03-1 differed genetically from the tumorigenic and non-antagonistic R. vitis strains (21, 26).…”
mentioning
confidence: 99%
“…We previously reported that the nonpathogenic R. vitis strain, VAR03-1, which was isolated from a grapevine nursery stock in Japan, inhibited tumor formation caused by several R. radiobacter (Ti), R. rhizogenes (Ti), and R. vitis (Ti) strains isolated from different plants in Japan on grapevines, roses, tomatoes, sunflowers, and apples (18, 19, 21, 22, 23, 25). Repetitive sequence-based polymerase chain reaction (rep-PCR) DNA fingerprint analysis and an analysis of the sequences of three housekeeping genes revealed that VAR03-1 differed genetically from the tumorigenic and non-antagonistic R. vitis strains (21, 26).…”
mentioning
confidence: 99%
“…Rhizobium vitis (Ti), Agrobacterium vitis (Ti), and A. tumefaciens biovar 3), where Ti means tumorigenic [ 1 , 2 ]. A. vitis (Ti) infects grapevines through wounds, such as freezing injuries, cutting damage, and grafting [ 3 , 4 , 5 , 6 , 7 , 8 ]. GCG is a pandemic throughout the world [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…GCG is a pandemic throughout the world [ 3 , 4 , 5 , 6 ]. Galls generally form on the trunks and cordons of young and mature grapevines [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Infected grapevines often experience inferior growth, but the galls cause grapevine death [ 7 ].…”
Section: Introductionmentioning
confidence: 99%